Application of electrospun nanofibrous amphiphobic membrane using low-cost poly (ethylene terephthalate) for robust membrane distillation. (August 2020) - Xu, Guo-Rong; An, Xiao-Chan; Das, Rasel; Xu, Ke; Xing, Yu-Lei; Hu, Yun-Xia
Graphical abstract: Herein, we fabricated a kind of eco-friendly and cost-effective electrospun nanofibrous membranes derived from Coca Cola bottles to solve the freshwater crisis by membrane distillation. Highlights: Low-cost PET derived from Coca Cola bottles was used as raw materials. PET electrospun nanofibrous membranes were used in membrane distillation (MD). Performance optimization was realized with controllable post heat-pressing. Amphiphobic modification makes membranes more applicable in MD. Abstract: Although with great potential, membrane distillation (MD) is still far from satisfaction due to deficiency of ideal membranes with low cost and high performance. In this work, electrospun nanofibrous membranes (ENMs) fabricated using polyethylene terephthalate (PET) derived from recycled Coca Cola plastic bottles were evaluated in direct contact (DC) MD application. Heat-pressing was used to tune physicochemical properties of PET ENMs to get them better qualified for MD. Effect of heat-pressing on membrane structure and properties was emphasized. The preferred PET ENMs with nanofiber diameter of 517 nm exhibited high porosity of 77 %, high hydrophobicity with contact angle of ≥130°, and high liquid entry pressure of water (LEPw ) of 49.8 kPa. The optimized PET ENMs displayed permeation of about 11−23 L m −2 h -1 (LMH) with varied temperature differences and salt rejection of 99.9 %. Stable permeation was noticed in the long-run membrane operation without significant permeation loss. Finally, 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane (FAS) was used to modify the surface of membrane to enhance their antiwetting capability against the oil. Surface modification rendered excellent endurance to the membrane even with addition of 0.3 M Sodium Dodecyl Sulfate (SDS, a model surfactant) while the pristine membrane failed to work once the SDS was added. This work paves the way for developing a low-cost and acceptable industrial-grade membrane with great potential in DCMD applications.